Towards virtual deformation dilatometry for the design of hot stamping process. (2017) - Bambach, M.; Buhl, J.; Hart-Rawung, T.; Lechner, M.; Merklein, M.
Abstract: Hot stamping is a well-established process for the production of structural automotive parts with an excellent strength-to-weight ratio. The complexity of the thermo-mechanical history in hot stamping requires a precise virtual design of hot stamping processes. The thermal and mechanical characteristics of the most common press hardening steel 22MnB5 were investigated comprehensively and are well represented by numerical models. For new steel compositions and parts involving tailored tempering, numerous experiments, e.g., on a deformation dilatometer or thermo-mechanical simulator are needed to characterise the microstructure evolution and the resulting properties. If appropriate material models were available, new steel compositions and thermo-mechanical histories could be partly explored virtually by simulated deformation dilatometer tests. This paper presents a comparison of experimental and virtual deformation dilatometer tests for the hot stamping steel 22MnB5. The virtual dilatometer is implemented as finite element model in the software LS-Dyna based on the material model *MAT248. With this model, virtual and real dilatometer curves correspond well only for conditions of full martensitic hardening, while pre-strains cause larger differences between model and experiments. When the most sensitive model parameters are formulated as a function of pre-strain, all experimental dilatometer curves can be reproduced by the model. Such a data-driven extension of the model seems to be effective for creating a virtual dilatometer model of high accuracy.